A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil - Soares, Isabel Matos; Bührnheim, Cristina Motta (Zootaxa, 2016)
A new species of Moenkhausia is described from tributaries of the lower Amazon basin, Pará State, Brazil. The new species is morphologically similar to Moenkhausia collettii, M. copei, and M. venerei by the presence of a dark horizontal stripe across the middle portion of the eye, a conspicuous slightly rounded humeral blotch, a dark longitudinal midlateral stripe and a dark stripe along the anal-fin base. However, the new species can be distinguished from M. collettii, M. copei, and M. venerei mainly by the number of cusps on the inner row of the premaxillary, maxillary and dentary teeth, and by the number of scales in transversal series above and below the lateral line.